2020
DOI: 10.1055/s-0039-3402052
|View full text |Cite
|
Sign up to set email alerts
|

Fat Processing Techniques

Abstract: Autologous fat grafting is an aesthetic and reconstructive procedure in which an individual's own fat is harvested and injected into the soft tissues to correct contour and other abnormalities. Fat graft is considered the ideal soft tissue filler for its biocompatibility, lack of immunogenicity, and availability. The entire procedure of harvesting, processing, and transfer of fat graft affects fat graft take and effectiveness of fat grafting. This article will focus on the most common methods of fat graft proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 32 publications
1
42
0
10
Order By: Relevance
“…Processing of adipose tissue prior to injection is hardly evidence-based. 2 In contrast to many studies using liposuction with centrifugation, we excise abdominal fat en masse. Fibrous attachments are sharply excised to reduce irregularity and scarring, while every attempt is made to maintain the integrity of adipocytes and preserve volume.…”
Section: Response To Letter To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Processing of adipose tissue prior to injection is hardly evidence-based. 2 In contrast to many studies using liposuction with centrifugation, we excise abdominal fat en masse. Fibrous attachments are sharply excised to reduce irregularity and scarring, while every attempt is made to maintain the integrity of adipocytes and preserve volume.…”
Section: Response To Letter To the Editormentioning
confidence: 99%
“…Countless methods of processing fat exist, none consistently superior. 2 These subtle differences may be less significant with pharyngeal augmentation compared to facial aesthetic injections, which require greater predictability. Nevertheless, multiple recent reviews have found a greater percentage of graft retainment (40% vs 60%) when fat is enriched with adipose-derived stem cells or platelet-rich plasma.…”
Section: Response To Letter To the Editormentioning
confidence: 99%
“…Numerous techniques for fat processing have been described and evaluated, including centrifugation, cotton gauze rolling, sedimentation, and filtration/washing [5]. A common goal of these techniques is to purify the fat in order to lower fat resorption as much as possible.…”
Section: Introductionmentioning
confidence: 99%
“…A common goal of these techniques is to purify the fat in order to lower fat resorption as much as possible. The reported fat resorption rate varies between 20 and 80% of the total injected volume [5]. Despite the considerable number of clinical studies on the topic, there is no real consensus about the most efficient way to process fat to achieve optimal results [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation